PENGARUH PENGGUNAAN DEBIT CARD DAN E-MONEY TERHADAP PERILAKU KONSUMTIF MAHASISWA PRODI EKONOMI ISLAM FAKULTAS EKONOMIKA DAN BISNIS UNESA - Muhammad Bilal Abdillah Rasyid; Fahrullah, (Jurnal Ekonomika dan Bisnis Islam, 2022)
This research was conducted to analyze whether there is an effect of using debit cards and e-money on the consumptive behavior of students of the Islamic Economics Study Program, Faculty of Economics, State University of Surabaya. The population of this research is students of the Islamic Economics Study Program, Faculty of Economics and Business, UNESA batch 2018, 2019, and 2020, totaling 174 students with the criteria of having taken financial management courses and with an allowance of Rp. 1,000,000. Determination of the sample by purposive sampling and a total of 121 students. Data collection through questionnaires. This research uses linear regression analysis through SPSS 25. From the research conducted, the researchers obtained the results that debit cards and electronic money partially or simultaneously have a positive and simultaneous effect on student consumptive behavior. This is evidenced by the results of the R Square analysis with a value of 67.2%. This means that the variables X1 (debit card) and X2 (e-money) simultaneously have an influence on variable Y (consumptive behavior) as much as 67.2% and at least 32.8% are influenced by variables outside of this research..